2019
DOI: 10.1002/ange.201908736
|View full text |Cite
|
Sign up to set email alerts
|

The Kirkendall Effect for Engineering Oxygen Vacancy of Hollow Co3O4 Nanoparticles toward High‐Performance Portable Zinc–Air Batteries

Abstract: Structure and defect control are widely accepted effective strategies to manipulate the activity and stability of catalysts. On a freestanding hierarchically porous carbon microstructure, the tuning of oxygen vacancy in the embedded hollow cobaltosic oxide (Co3O4) nanoparticles is demonstrated through the regulation of nanoscale Kirkendall effect. Starting with the embedded cobalt nanoparticles, the concentration of oxygen‐vacancy defect can vary with the degree of Kirkendall oxidation, thus regulating the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(37 citation statements)
references
References 37 publications
(15 reference statements)
2
32
0
Order By: Relevance
“…Note that ZABs (Zn 3 Mn) and ZABs (Zn) are used to represent the batteries using Zn 3 Mn and Zn anodes, respectively, to reduce the wordy description. At a high current density of 30 mA cm −2 , the ZABs (Zn 3 Mn) delivered an extremely high discharge capacity of 816.3 mAh g Zn −1 corresponding to an energy density of 798.3 Wh kg Zn −1 , higher than those of ZABs (Zn; 784 mAh g Zn −1 and 657 Wh kg Zn −1 ) and superior to the recent benchmarking ZABs 49 51 . The significantly improved performance of the ZABs (Zn 3 Mn) is ascribed to the sufficiently exposed active areas in the hierarchically porous 3D architectures via this surface/interface engineering 52 .…”
Section: Resultsmentioning
confidence: 94%
“…Note that ZABs (Zn 3 Mn) and ZABs (Zn) are used to represent the batteries using Zn 3 Mn and Zn anodes, respectively, to reduce the wordy description. At a high current density of 30 mA cm −2 , the ZABs (Zn 3 Mn) delivered an extremely high discharge capacity of 816.3 mAh g Zn −1 corresponding to an energy density of 798.3 Wh kg Zn −1 , higher than those of ZABs (Zn; 784 mAh g Zn −1 and 657 Wh kg Zn −1 ) and superior to the recent benchmarking ZABs 49 51 . The significantly improved performance of the ZABs (Zn 3 Mn) is ascribed to the sufficiently exposed active areas in the hierarchically porous 3D architectures via this surface/interface engineering 52 .…”
Section: Resultsmentioning
confidence: 94%
“…Previous reports have shown that the hollow structure can be formed through hard-templated, soft-templated and selftemplated routes 22 . The use of presynthesized solid templates containing at least one of the elements of the final nanoshell usually results in a mechanism analogous to the nanoscale Kirkendall effect 32,37 . The process first includes the reaction of the elements (A) in the template with the external reagents (B) to produce a layer of shell materials (AB).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the Cu@C was treated at 300 o C in air for a short time of 30 min to enable the insufficient oxidation of Cu NPs via a slow Kirkendall procedure (3 rd in Figure 1a and the similar result that the inadequate oxidation induces the formation of O v is also reported in other literatures. 30 Notably, the strategy that tunes the concentration of O v via the slow Kirkendall effect does not impact the microstructures of resulting samples (i.e., the similar hollow structure), proving great convenience for studying the effect of O v on the performance of NO 3 -RR.…”
Section: Resultsmentioning
confidence: 99%